Challenges in Implementing Neighborhood Layout Plans in Minor Towns: A Case of Mlowo Township, Songwe - Emmanuel E. Mchome; Uwezo W. Nzoya (Recent Research Advances in Arts and Social Studies Vol. 6, 2024)
This study has focused to answer the question of what and how the traits or characteris-tics of landholders (education, income, economic activities and awareness) influence the failure of implementation of the prepared neighborhood layout plans in minor towns. The main parties involved in creating and carrying out the neighborhood layout plans are the landowners. Various legal papers express their interest in ensuring that the plans are drafted and carried out in practice. As a result, these plans are created for metropolitan regions where the legal papers offer guidelines for planning techniques and space criteria. However, the same planning approaches and standards are used in both major and minor towns while landholders between the two have different traits leading to unrealistic planning process and poor implementations of the prepared plans in the minor towns. Literature reveals that landholders in minor towns possess unique traits or characteristics which differentiate them from those in major urban centres. The assessment was conducted with the help of crosstabs whereby different selected traits such as income, education, and awareness were cross-tabulated with aspects of plan preparation and implementation process, including surveying of plots, participation in plans preparation, services provision and title deeds acquisition. The results reveal that there is a significant relation between traits of land owners and developers and there is failure of implementation of the prepared layout plans in minor towns. Then, thinking on reversing the situation in these settlements should go simultaneous with strong strategies to transform the community living in minor towns so that they are exposed to the planning and land development process. The Government should promote education sector in the minor towns by increasing the number of high learning institutions that will increase the interaction of the landholders and people from other major urban centres which will help then wipe aware their cultural believes that hinder new technologies and approaches used in land development.